2010
DOI: 10.1007/s10530-010-9857-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cold hardiness among geographic populations of the ragweed beetle, Ophraella communa LeSage (Coleoptera: Chrysomelidae), a biological control agent of Ambrosia artemisiifolia L. (Asterales: Asteraceae), in China

Abstract: The ragweed beetle, Ophraella communa, is a potential biological control agent of common ragweed that appeared in Nanjing City in 2001 and has since dispersed throughout southeast China. We compared the cold hardiness of five different O. communa populations by measuring the supercooling point (SCP), water and glycerol contents of adult beetles. All indices of cold hardiness varied significantly among the sampled populations. Male beetles from the most northerly population (Nanjing) had the lowest water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…This results in bettles to have lower supercooling points when parents experienced colder temperatures. It has been demonstrated that cold hardiness, via changes in the relative composition of their body fluids and fats, is a plastic trait that can be influenced by fluctuations in abiotic factors (e.g., temperature) throughout the breeding season of O. communa [37], [38]. The present experiment is in line with the idea that O. communa has strong environmentally-driven phenotypic plasticity to cold adaptation, and this can be transmitted to the next generation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This results in bettles to have lower supercooling points when parents experienced colder temperatures. It has been demonstrated that cold hardiness, via changes in the relative composition of their body fluids and fats, is a plastic trait that can be influenced by fluctuations in abiotic factors (e.g., temperature) throughout the breeding season of O. communa [37], [38]. The present experiment is in line with the idea that O. communa has strong environmentally-driven phenotypic plasticity to cold adaptation, and this can be transmitted to the next generation.…”
Section: Discussionsupporting
confidence: 87%
“…Insects living in temperate regions have to cope with low winter temperatures, which may strongly influence the establishment and persistence of perennial populations in the field [37], [38], [58]. In general, survival rates of insects decrease with decreasing temperatures [23], [25], [27], [59], and this phenomenon has been also observed in O. communa [17], [23], [42].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For A. itadori to overwinter successfully in the UK, the climatic conditions must fall within the fundamental tolerances of the species and there must be suitable overwintering sites available. There will be a natural variation in the coldhardiness of any species depending on the conditions of the native region (Zhou Guo, Michaud, Li, & Wan, 2010). This can influence the selection of a particular population, not just the species identity, of a biological control agent to ensure the best match between the native and introduced regions.…”
mentioning
confidence: 99%